Efecto de tres densidades de siembra y dos tipos de fertilización, en el crecimiento y rendimiento del cultivo de maní (Arachis hypogaea L. var. Rosita) en Zapotepamba, provincia de Loja - Jara Tamayo, Jinsop Leonardo (2023)
The present research work was carried out at the Centro Binacional de Formación Técnica Zapotepamba, Paltas canton, province of Loja, with the objective of studying the effect of three planting densities and two types of fertilization (organic and chemical) on the growth and yield of the peanut crop (Arachis hypogaea L. var. Rosita). For its development, a Completely Random Block Design (CRBD), with bifactorial arrangement, the same, was used with six treatments and four repetitions (24 experimental units). The treatments used were the following: T1 (Density 1: 0.40 x 0.40 cm – organic: nutrisan); T2 (Density 2: 0.50 x 0.40 cm - 0rgánica: nutrisano); T3 (Density 3: 0.40 x 0.30 cm - 0rgánica: nutrisano); T4 (Density 1: 0.40 x 0.40 cm – chemistry: Blaukorn 12-8-16+ Folizyme + Urea 46%N); T5 (Density 2: 0.50 x 0.40 cm – chemistry: Blaukorn 12-8-16+ Folizyme + Urea 46%N); T6 (Density 3: 0.40 x 0.30 cm – chemistry: Blaukorn 12-8-16+ Folizyme + Urea 46%N); The variables evaluated were phenology, growth variables, yield and production costs. For the statistical analysis of data, the InfoStat software was used, using analysis of variance (ANOVA), for statistical differences a Tukey test was used at 95%, a Pearson correlation at 95% and in turn the benefit-cost ratio was calculated. The phenological stages did not present statistically significant differences between the treatments with respect to the duration of each of them, as well as the variables of emergence, dry and root biomass, number of branches and seed diameter. The variables that presented statistically significant differences were: plant height, with T6 being the maximum value of 39.99 cm; stem diameter showed T4 with 7.62 mm; number of nodules with 712; root length at T6 at 20,35 cm, Weight of 100 pods at T6 240,50 g, weight of 100 seeds T6 at 61,75 g, number of pods/plant at T6 16,80, pod length at T3 at 4,22 cm, pod diameter at T6 at 1,38 cm, seed length at T5 1,47 cm. The highest yield presented the T6 treatment with 2.88 t/ha. Regarding the benefit-cost analysis, the T6 treatment obtained a value of 1.32 and T3 1.05, proving to be the most profitable. Keywords: Fertilization, Arachis hypogaea, phenology, yield, benefit-cost.